ACCOUNTING AS TAUGHT AT ANTIOCH. - Henderson, A. D. (The Accounting Review, 1927)
Abstract The accounting course is distinctive in four respect. Probably the least important of these lies in the nature of the departmental organization. The business courses are divided into two departments, based on operating and non-operating business functions. The former include marketing, purchasing, and production, the latter, accounting, statistics, and finance. One have found that the general subject matter in the department of accounting and finance harmonizes with excellent effect, aid that courses are given with a minimum of overlapping material. Internal statistics are the product of the system of records in any given business. External statistics are largely the product of records of other companies. In discussing problems in business finance, therefore, such things as financial conditions, ratios and application of funds, and bond issues, are studied without the usual handicap of distinguishing between accounting method and financial policy. In the introductory course of the department the students get training in the preparation of a budget, the keeping of accounts, and the use of banking facilities.